Effects of cutaneous leishmaniasis on health-related quality of life: A longitudinal approach - Endi Lanza Galvão; Janaína de Pina Carvalho; Tália Santana Machado de Assis; Gláucia Cota; Sarah Nascimento Silva (PLoS ONE, 2025)
Introduction Cutaneous leishmaniasis (CL) is a neglected tropical disease that significantly affects patients’ physical, psychological, and social well-being. Although previous studies have documented health-related quality of life (HRQoL) impairments associated with CL, most have relied on cross-sectional data, providing only a snapshot of the disease burden. Few studies have examined HRQoL progression over time or explored treatment effects from the patient’s perspective. Objectives This study aimed to evaluate changes in HRQoL among CL patients at three time points: before treatment, during treatment, and after treatment, using the Cutaneous Leishmaniasis Impact Questionnaire (CLIQ). Methods A longitudinal observational study was conducted from October 2020 to April 2023 at a specialized center in Belo Horizonte, Brazil, involving 143 CL patients. The CLIQ was administered at diagnosis, during treatment (up to 30 days post-treatment), and at least 90 days after treatment initiation. Analyses included descriptive statistics, group comparisons using nonparametric methods, and correlation assessments based on rank-order relationships. Findings Of the 143 patients enrolled, 120 completed all assessments. Median CLIQ scores improved significantly from pre-treatment (24, IQR 16–36) to post-treatment (15, IQR 8.25–25; p < 0.001). Notable improvements were observed in physical symptoms, emotional distress, and daily functioning. However, financial burden and social isolation persisted after treatment. Patient dissatisfaction with health services peaked during treatment but decreased afterward. Conclusion Treatment significantly enhanced HRQoL in CL patients, particularly in the physical and functional domains. Nevertheless, persistent financial and emotional challenges underscore the need for comprehensive support interventions addressing economic and psychosocial dimensions, thereby promoting holistic care.